Marine Tourism Benefit from Economic Perspective (Case in Pari Island, Indonesia) - Agnes Puspitasari Sudarmo (Research Collaboration Community (RCC), 2020)
Marine tourism as new emerging economic icon had potential economic growth to promote Indonesia’s economic development. One of the islands that attract many visitors who want to enjoy marine tourism is Pari Island, which lies in Kepulauan Seribu, Jakarta. The study was conducted in June 2017 until October 2017 on Pari Island, Kepulauan Seribu, Jakarta. The research method used is descriptive. Sample was tourist from domestic as well as foreign countries who travelled to Pari Island. Data collection was gathered by survey techniques, which are complemented by observation, and interviews. For data collection using survey techniques, only respondents who were willing were given a questionnaire to fill out the questionnaire. Data was analyzed using descriptive and PCA.